STUDI KELAYAKAN BUDIDAYA CACING TANAH BERBASIS JAMINAN PRODUK HALAL DI BARRU SULAWESI SELATAN - Dedi Setiawan; Andi Pawennari; Arminas Arminas; Ahmad Firman; Muhammad Nusran (Universitas Mathla’ul Anwar Banten, 2022)
Today, earthworms have a huge potential to be cultivated professionally for commercial business purposes. This earthworm business business is very beneficial for the benefit of the animal and fish feed industry, the needs of the pharmaceutical industry. Earthworms are commodities that are useful both for soil fertility and for the world of medicine. Treatment by using earthworms has been widely attempted in the community, even according to the MUI in the MUI Fatwa Number: 139 year 2000, confirming that the law is permissible (mubah). The purpose of this research is to find out a feasibility study for the establishment of an earthworm cultivation business to meet market demand which is currently still low. Data were taken from interviews and analysis using 5 aspects to determine the location of the earthworm cultivation business. Based on the analysis of the market aspect of earthworm cultivation in Barru district using the linear regression method of forecasting where the production capacity in 2021 is 1,779 with a production plan of 10%. In market share per year. The conclusion is that the law using worm extracts is permissible meaning that it is halal to try and consume the results of worm extracts for treatment, then on the financial aspect that IRR > MARR is 37.06% > 6%, it can be said that the establishment of an earthworm cultivation business in the district just worth continuing.